2015
DOI: 10.1111/exd.12740
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of stratum corneum lipid composition and organization of human skin equivalents by specific medium supplements

Abstract: Our in-house human skin equivalents contain all stratum corneum (SC) barrier lipid classes, but have a reduced level of free fatty acids (FAs), of which a part is mono-unsaturated. These differences lead to an altered SC lipid organization and thereby a reduced barrier function compared to human skin. In this study, we aimed to improve the SC FA composition and, consequently, the SC lipid organization of the Leiden epidermal model (LEM) by specific medium supplements. The standard FA mixture (consisting of pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Nevertheless, as reported by other groups, these skin substitutes showed a decreased permeability barrier compared with human skin when performing diffusion studies [46]. Our results showed that cumulative amounts were not significantly different between fresh and frozen human skin samples where both showed good barrier against benzoic acid (Figure 2A), which is in accordance with the literature [44].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, as reported by other groups, these skin substitutes showed a decreased permeability barrier compared with human skin when performing diffusion studies [46]. Our results showed that cumulative amounts were not significantly different between fresh and frozen human skin samples where both showed good barrier against benzoic acid (Figure 2A), which is in accordance with the literature [44].…”
Section: Discussionsupporting
confidence: 92%
“…Although all lipid classes present in native human skin are also present in HSEs, there is a deviation in free lipid composition and organization compared to native human skin. The most important of such deviations are a high level of unsaturated fatty acids, shorter lipid chain lengths (Mojumdar et al, 2014;Thakoersing et al, 2013Thakoersing et al, , 2015 and an imbalance in the level of ceramide subclasses (Thakoersing et al, 2012). These changes in lipid composition are expected to contribute significantly to the impaired skin barrier of HSEs (Mojumdar et al, 2014).…”
Section: Tab 1: Models For Dermal Absorptionmentioning
confidence: 99%
“…According to Thakoersing et al [46] stratum corneum lipids of skin substitutes adopt a mainly hexagonal packing, whereas human stratum corneum lipids are arranged in a more dense orthorhombic packing [46]. However, ATR-FTIR results showed a good lipid organization correlation of both conditions: …”
Section: Discussionmentioning
confidence: 98%
“…At 28 °C, no significant differences in terms of lipid composition and organization were observed between fresh and frozen/thawed skin biopsy #23 (2849. 46 ). Finally, no significant differences were observed in this range of temperatures (Figure3A).…”
Section: Atr-ftir Spectroscopy Of Fresh and Frozen/thawed Human Skin mentioning
confidence: 99%